Relationship between profit after tax and corporate social responsibility expenditure in selected banks and manufacturing firms in Nigeria (Journal of Economic Research & Business Administration, 2020)
This is a comparative study of the effect of Profit After Tax (PAT) on Corporate Social Responsibility(CSR) expenditure in selected banks and manufacturing firms in Nigeria. A survey research design was usedwhile a purposive sampling method was employed to select ten organizations. Specifically, a longitudinalsurvey research design was used for the study. This approach was chosen based on the purposes, natureand the variables that were examined. The data collected and analyzed through content analysis helped toreveal trends or changes in the subjects over the period of time under study. Secondary data were garneredfrom annual reports and accounts of selected companies for a decade, i.e. 2010 to 2019. Inferential statisticswas used to analyse the data while the hypotheses were tested by correlation, ANOVA, and PooledOrdinary Least Square (OLS). Result shows F = 35.37 and p = 0.043. Since pvalue is less 0.05, the fstatisticsis significant. Hence, there is a significant difference between PAT and CSR expenditure in selectedorganizations. The study recommends that there should be an adjustment to the existing tax law in thecountry so that all expenditure on all form of CSR initiatives could be classified as tax deductible expenses.